If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7 = 4x + 7 Reorder the terms: 7 + 3x = 4x + 7 Reorder the terms: 7 + 3x = 7 + 4x Add '-7' to each side of the equation. 7 + -7 + 3x = 7 + -7 + 4x Combine like terms: 7 + -7 = 0 0 + 3x = 7 + -7 + 4x 3x = 7 + -7 + 4x Combine like terms: 7 + -7 = 0 3x = 0 + 4x 3x = 4x Solving 3x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 3x + -4x = 4x + -4x Combine like terms: 3x + -4x = -1x -1x = 4x + -4x Combine like terms: 4x + -4x = 0 -1x = 0 Divide each side by '-1'. x = 0 Simplifying x = 0
| 10x-2=9(x+3)+9 | | 14x+5-13x=-20 | | 8x-11=7x+2 | | 11(x-2)-11=23x-177 | | x+3(19x+76)= | | 2x-4=9x-32 | | -9x-63=21-6x | | x^2-18x+81+3x^4-27=0 | | -4(5n+1)=8 | | 6x+4y=-8 | | 11(x-11)-2=15X-139 | | 2x+4x-4=44 | | -2(2n+2)=2 | | 42+3x=6 | | 11(x-8)-3=18x-168 | | x^2-18x+81+3x^4-27x^3=0 | | x+4x=25 | | 2x+8=-1x-4 | | 4x^2-6x+57=19 | | 7x-y=8 | | 71a+18c=11 | | 4x+8=6x-10 | | 4x+3=13+2x | | x^2-16x+64+6x^8-48x^7=0 | | 2w+2(2w-4)=76 | | 8x-2=4x-10 | | 6x+7=3x-2 | | x^2+12x-2=0 | | 5(3z-1)-3(z+2)=2(2+1) | | 6x+2=4x-4 | | 44a-16a-5(a+6)-9=6 | | 5x+5(4)=20 |